Extraction, purification and characterization of green mussel Perna viridis foot protein-3 (pvfp-3) - Kwan, Kerby Cheuk Hay (2011)
Green mussel (Perna viridis) are known to secrete precursor adhesive proteins that enable them to stick tenaciously to submerged surfaces. A total of eight proteins have been discovered upon the analysis of the adhesive plaque from other mussel species. The aim of this project is to examine a specific protein from the green mussel, named Pvfp-3, as MALDI-based molecular weight analysis previously indicated a significant amount of this particular protein at the adhesive plaque/surface interface. Post-translational modified tyrosine L-dihydroxyphenylalanine (DOPA) protein is believed to play a major role in the adhesion and rapid cross-linking that enables the plaque to adhere to the substrate viciously.